Dry beans and pulses production, processing and nutrition. - Siddiq, Muhammad, 1957-; Uebersax, Mark A. (Wiley, 2022)
"This second edition is updated throughout to incorporate the latest research, consumer trends, new products, and food security issues, and features four new chapters: Hard-to-cook phenomenon and other storage induced quality defects in dry beans and pulses Quality assessment of raw and processed legumes using innovative technologies Utilization of dry beans and pulses as ingredients in diverse food product Faba bean production, processing, products and nutritional profile Blurb for the first edition: Dry Beans Production, Processing and Nutrition provides a contemporary source of information that brings together current knowledge and practices in the value chain of dry beans production, processing, and nutrition. Coverage is extensive and includes production/postharvest technologies; value-added processing and packaging technologies; nutrition and significance in human health; and quality management. In addition to conventional products, the book covers new technologies for beans -- minimally processed bean products, bean-based extruded snacks, and the latest nutritional and human health interventions utilizing dry beans. The diverse nutritional properties of dry beans, especially antioxidant properties, are explored for their applications as functional foods, gluten-free alternatives and as weight management aids. Covering both traditional and non-traditional bean classes produced and consumed worldwide, Dry Beans Production, Processing and Nutrition is an essential resource for scientists, processors and nutritionists, whatever the work setting"--